2008
DOI: 10.1002/pits.20303
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement with school: Critical conceptual and methodological issues of the construct

Abstract: Research supports the connection between engagement, achievement, and school behavior across levels of economic and social advantage and disadvantage. Despite increasing interest and scientific findings, a number of interrelated conceptual and methodological issues must be addressed to advance this construct, particularly for designing data-supported interventions that promote school completion and enhanced educational outcomes for all students. Of particular concern is the need to (a) develop consensus on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
959
0
127

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,301 publications
(1,188 citation statements)
references
References 51 publications
24
959
0
127
Order By: Relevance
“…Numerous number of models been proposed to describe the various aspects of engagement. Nevertheless, despite the fact that different models accentuate different aspects of engagement, there are substantial overlaps and similarities among them [4], [5]. In a major literature review, Fredricks et al [5] identified three main aspects of engagement -a) behavioral engagement which refers to students participating in a learning activity such as completing an assignment, attending classes, or contributing in discussions, b) affective engagement which refers to students" emotional responses or feeling (positive or negative) toward teachers, peers, learning, and school, and c) cognitive engagement which refers to "the deliberate task-specific thinking that a student undertakes while participating in an activity" [6].…”
Section: A Engagementmentioning
confidence: 99%
“…Numerous number of models been proposed to describe the various aspects of engagement. Nevertheless, despite the fact that different models accentuate different aspects of engagement, there are substantial overlaps and similarities among them [4], [5]. In a major literature review, Fredricks et al [5] identified three main aspects of engagement -a) behavioral engagement which refers to students participating in a learning activity such as completing an assignment, attending classes, or contributing in discussions, b) affective engagement which refers to students" emotional responses or feeling (positive or negative) toward teachers, peers, learning, and school, and c) cognitive engagement which refers to "the deliberate task-specific thinking that a student undertakes while participating in an activity" [6].…”
Section: A Engagementmentioning
confidence: 99%
“…A multidimensional view of the engagement construct (Appleton et al, 2008;Appleton et al, 2006) highlights its complexity as it is often regarded as a meta-construct (Axelson & Flick, 2011;Jimerson et al, 2003;Lam et al, 2012;Sinclair et al, 2003). Specifically, Fredericks et al (2004) identified three dimensions of student engagement that included behavioral, emotional, and cognitive factors; a conceptualization echoed by Marx, et al (2016) in their examination of student course engagement.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…As a result, a variety of definitions and conceptualizations of what is meant within the engagement literature have been extended. Several researchers have promulgated this issue in recent years (Appleton, et al, 2008;Axelson & Flick, 2011;Bowen, 2005;Shulman, 2002). Specifically, Bowen (2005) declared that a consensus on what is meant by engagement or why it is important is nonexistent, while Shulman (2002) posited that learning begins with engagement, therefore making it one of the most important aspects in the learning process.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…cognitive and affective engagement (Appleton, Christenson, & Furlong, 2008). Cognitive engagement is defined as motivation and investment in the process of learning whereas affective engagement is having feelings of pride and attachment to school (Appleton et al, 2008).…”
Section: Student Engagementmentioning
confidence: 99%
“…Cognitive engagement is defined as motivation and investment in the process of learning whereas affective engagement is having feelings of pride and attachment to school (Appleton et al, 2008). Student engagement has been positively associated with higher achievement and negatively associated with factors related to achievement such as school dropout and truancy (Fredricks, Blumenfeld, and Paris, 2004;Marks, 2000).…”
Section: Student Engagementmentioning
confidence: 99%